Professors Feedback trough ICT and Students’ Perceptions in Secondary Education - Moreno Romero, Liliana Leticia (2022)
The objective of this research was to characterize the virtual feedback offered by the professors in contrast to the perceptions of the students. The investigation was developed under a qualitative and quantitative paradigm and the participants were two teachers of post-compulsory secondary education and their students. Moreover, the authors carried out a content analysis of the interviews and feedback, as well as a descriptive statistical analysis of satisfaction questionnaires. The results show the need to attend to the characteristics, interests, and needs of the students when planning the delivery of feedback with the use of Information and Communication Technologies (ICT), which influences the perceptions and use of the feedback received.